2017
DOI: 10.18632/oncotarget.22712
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-enhanced stemness and epithelial-mesenchymal transition of human umbilical cord mesenchymal stem cells promote tumor formation and growth in nude mice

Abstract: Cigarette smoking is a well-known risk factor in the development and progression of malignant diseases. Nicotine, the major constituent in cigarette smoke, has also shown negative effects on stem cells. Mesenchymal stem cells (MSCs) have been widely demonstrated to migrate into tumors and play key roles in cancer progression. However, the mechanisms by which nicotine impacts MSCs and tumorigenesis of lung cancer are still undetermined. In this study we investigated the effects of nicotine on human umbilical co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…It is well known that the use of combustible tobacco products increases the risk for a malignancy; however, nicotine alone may contribute to treatment resistance and cancer progression. 126,127 An in vitro study using human umbilical cord mesenchymal stem cells treated with nicotine revealed increased migration, enhanced stemness, and increased epithelialmesenchymal transition (EMT), 128 consistent with cellular processes that promote tumor progression. In another study, nicotine induced EMT of breast cancer cells and activated fibroblasts, which enhanced EMT and cancer cell migration.…”
Section: Nicotine and Malignancymentioning
confidence: 87%
“…It is well known that the use of combustible tobacco products increases the risk for a malignancy; however, nicotine alone may contribute to treatment resistance and cancer progression. 126,127 An in vitro study using human umbilical cord mesenchymal stem cells treated with nicotine revealed increased migration, enhanced stemness, and increased epithelialmesenchymal transition (EMT), 128 consistent with cellular processes that promote tumor progression. In another study, nicotine induced EMT of breast cancer cells and activated fibroblasts, which enhanced EMT and cancer cell migration.…”
Section: Nicotine and Malignancymentioning
confidence: 87%
“…E-cigarette, nicotine patch, and nicotine gum are nicotine replacement therapies for smoking cessation used by these patients ( Hartmann-Boyce et al, 2018 ; Stead et al, 2012 ). Although nicotine, per se, is not a carcinogen, many reports document its tumor-promoting effects ( Li et al, 2017 ; Schaal and Chellappan, 2014 ; Schaal et al, 2018 ) as well as its pro-inflammatory effect, which suppresses the phagocytosis ability of the alveolar macrophages ( Scott et al, 2018 ). Considering our results that clearly demonstrated profound and long-term effects of nicotine on brain metastasis progression, extra caution should be paid in the use of nicotine for smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh umbilical cords were collected from healthy donors after obtaining informed consent at the Affiliated Hospital of Jiangsu University. hUC-MSCs were isolated and cultured as described in our previous studies (8,21,31). In brief, umbilical cord blood vessels were carefully removed to retain Wharton's jelly, and the remaining tissue was then cut into 1-mm 3 sized sections with scissors and placed in low glucose Dulbecco's modified Eagle's medium (L-DMEM) (cat.…”
Section: Methodsmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are multipotent stem cells that can be derived from various tissues, including the umbilical cord, bone marrow and adipose tissue (8)(9)(10)(11). MSCs have the potential to differentiate into various cell types of the mesodermal germ layer, including osteoblasts, adipocytes and chondrocytes (12,13).…”
Section: Introductionmentioning
confidence: 99%